Investigating clotting changes in patients from Steve Biko Academic Hospital with intracerebral haemorrhage by studying the viscoelastic and ultrastructural properties of whole blood. - Bester, Janette (University of Pretoria, 2024)
Dissertation (Msc (Human Physiology))--University of Pretoria, 2023.